Development of capability for genome-scale CRISPR-Cas9 knockout screens in New Zealand. Issue 4 (2nd October 2018) - Hunter, Francis W.; Tsai, Peter; Kakadia, Purvi M.; Bohlander, Stefan K.; Print, Cristin G.; Wilson, William R.
ABSTRACT: The discovery of CRISPR-Cas systems in prokaryotic adaptive immunity has provided a veritable cornucopia of molecular biology tools. Here, we review the remarkable adaptation of CRISPR-Cas as a toolkit for gene editing in eukaryotes, with applications ranging from gene knockout, genetic and epigenetic modification, tagging and isolation of specific loci to functional genomics. We also report the development of capability for performing genome-scale CRISPR knockout screens within New Zealand. An efficient CRISPR functional genomics pipeline has been installed at the University of Auckland, where the cellular and molecular biology, next-generation sequencing and bioinformatic components of the screening workflow have each been extensively optimised. This platform has been made available to New Zealand scientists and provides a powerful tool for unbiased discovery of genetic contributions to a universe of cell biological phenotypes including, for example, the responsiveness of cancer cells to therapy.